Racial and Ethnic Differences in Mental Illness Stigma and Discrimination Among Californians Experiencing Mental Health Challenges - Wong, Eunice C. (RAND Corporation, 2016)
Reports racial and ethnic differences on the California Well-Being Survey, a surveillance tool that tracks mental illness stigma and discrimination among a sample of California adults experiencing psychological distress.